Food for thought : recipes for ultimate mind and body health - Ferrare, Cristina (Post Hill Press, 2018)
With her simple, creative recipes, you can explore everything from the importance of a nutritious breakfast to the surprising ways that the shape of a food can give us clues about the part of our body it will nourish. Take the first step towards ultimate health with Food for Thought and join Ferrare in the kitchen as she teaches you how eating the foods you love can keep you healthy, vital, and strong.